Acenaphtho[1, 2‐d][1, 2, 3]triazole and Its Kuratowski Complex: A π‐Extended Tecton for Supramolecular and Coordinative Self‐Assembly. Issue 4 (2nd December 2021) - Knippen, Katharina; Matuszczyk, Daniel; Kraft, Maryana; Bredenkötter, Björn; Eickerling, Georg; Lis, Tadeusz; Volkmer, Dirk; Stępień, Marcin
Abstract: π‐Extended acenaphtho[1, 2‐ d ][1, 2, 3]triazoles, the unsubstituted Anta‐H and its di‐ tert ‐butyl derivative Dibanta‐H, as well as 5, 6, 7, 8‐tetrahydro‐1 H ‐naphtho[2, 3‐ d ][1, 2, 3]triazole Cybta‐H were obtained in concise syntheses. In the solid state, Dibanta‐H forms an unprecedented hydrogen‐bonded cyclic tetrad, stabilized by dispersion interactions of the bulky t Bu substituents, whereas a cyclic triad was found in the crystal structure of Anta‐H. These cyclic assemblies form infinite slipped stacks in the crystals. Evidence for analogous hydrogen‐bonded self‐assembly in solution was provided by low‐temperature NMR spectroscopy and computational analyses. Kuratowski‐type pentanuclear complexes [Zn5 Cl4 (Dibanta)6 ] and [Zn5 Cl4 (Cybta)6 ] were prepared from the respective triazoles. In the Dibanta complexes, the π‐aromatic surfaces of the ligands extend from the edges of the tetrahedral Zn5 core, yielding an enlarged structure with significant internal molecular free volume and red‐shifted fluorescence. Abstract : Two‐ and three‐dimensional structures can be assembled from π‐extended triazoles, which act as versatile tectons capable of metal coordination, hydrogen bonding, and π‐stacking interactions. Infinite stacks of cyclic hydrogen‐bonded tetrads or triads are obtained in the crystal, with substitution controlling the size of the assembly. In spite of their bulkiness, π‐extended triazoles easily form pentanuclear zinc(II) Kuratowski complexes, characterized by concave outer surfaces and moderate solid‐state porosity.